Players` decisions within ball screens in elite German men`s basketball: observation of offensive-defensive interactions using a process-orientated state-event model - Remmert, H.; Chau, A.-T. (International Journal of Performance Analysis in Sport, 2019)
Ball screens have become more important in basketball since the shot clock`s 24-s limitation in 2000. To quantify the percentage of ball screens in German elite men`s basketball and success rates of concrete offensive ball screen finishing solutions, we observed 12 play-off-games of the German "easyCredit Basketball Bundesliga" season 2016/17 using observational categories that describe the detailed offensive-defensive interactions within ball screens. In total, 1821 offensive sequences producing 1.03 points in average have been counted. Ball screens are used in 55.4% of any offense to finish offensive sequences with an overall success rate of 1.01 points per offense, 89.4% of them being active screens. Ball screens are most successful when defenders act passively (remaining in the screens shadow and sagging under the screen). The ball handler`s shot and the screener`s pop out are the most successful finishing actions. Winning teams scored more effectively from active and dribble screens and show an advantage in average points scored from ball screens, they also defend more effectively. We recommend youth players to adapt to the broad variety of ball screen actions and perfect their ball handling and shooting skills in the long term.